A Qur'anic Exploration of Moral Absolutism and Moral Relativity - Ali akbar Hoseyni ramandi; Mohammad Mahdi Firoozmehr (اخلاق وحیانی, 2024)
The discussion about the Moral Absolutism and Moral relativity begins with this question: do moral rules change with the change of conditions, time, place, people and societies, or are they always fixed and without any restriction and allocation, including all people, in all times and places?Some schools consider moral rules to be a relative matter, whose rules will change with the change of conditions, time, place, people and societies; but a number of schools consider moral laws to be fixed, eternal and independent of time, place, conditions and people.The present research is an exploration about the application and moral relativity in the scope of the Quranic revelation. Quranic teachings shows that the moral system of Islam is based on fixed and absolute laws and rulings, and numerous Quranic reasons and evidences support the Moral Absolutism principles and do not reflect moral relativism.